Effect of mineral oil as a lubricant to collect feces from cats for microbiome studies. (1st October 2022) - Ma, Xiaolei; Brinker, Emily; Cao, Wenqi; Graff, Emily C.; Wang, Xu
Abstract: Background: Fecal specimens are critical for disease screening, diagnosis, and gut microbiome research. For domestic cats, lubricants are often necessary to obtain a sufficient quantity of sample. However, the effect of lubrication on feline microbiome analysis has not been assessed. Objectives: To evaluate if lubrication using mineral oil during cat feces sample collection affects the DNA extraction, metagenomic sequencing yield, and the microbial composition and diversity in subsequent gut microbiome analyses. Animals: Eight 6‐year‐old male, neutered, domestic short‐haired cats housed in a research facility. Methods: Cohort study. The gut microbiomes were investigated for fecal sample collection with and without lubrication using whole‐genome shotgun metagenomic sequencing. Results: Fecal specimens were collected using a fecal loop under sedation without lubrication and with mineral oil lubrication. There were no significant differences between the 2 groups in the microbial DNA yield in ng/mg fecal sample (75.75 [25.8‐125.7] vs 60.72 [33.49‐87.95], P  = .95), metagenomic sequencing yield in Gbp (10.31 [6.29‐14.32] vs 13.53 [12.04‐15.02], P  = .2), proportion of host contamination (0.1 [0.02‐0.18] vs 0.15 [0‐0.3], P  = .84), relative taxonomy abundance ( P  > .8), or the number of microbial genes covered (408 132 [341 556‐474 708] vs 425 697 [358 505‐492 889], P  = .31). Conclusions and Clinical Importance: Fecal sampling with mineral oil lubrication did not change the microbial DNA extraction yield, metagenomic sequencing yield, level of host contamination, the microbial composition and diversity in subsequent gut microbiome analyses. Here we reported a proven cat‐friendly protocol for fecal sample collection in clinical and research setting for gut microbiome analyses.